Gender and ethnicity's influence on first‐year nursing students' educational motivation and career expectations: A cross‐sectional study - Sigurd Maurud; Elin Børøsund; Anne Moen (Nursing Open, 2022)
Abstract Aim Given the apparent link between gender and ethnicity, and the diversity and career opportunities in nursing, this study examined gender and ethnicity's influence on first‐year nursing students' educational motivation and career expectations. Design Cross‐sectional. Methods Through bootstrapped linear regressions, we analysed data on 504 Norwegian first‐year nursing students' self‐reported educational motivation and career expectations, from the StudData survey at the Centre for the Study of Professions (SPS) at Oslo Metropolitan University (OsloMet). Results The sample consisted of 67 (13%) male and 437 (87%) female nursing students. Female students were more motivated compared to male students by professional interest and to pursue a specialization, less likely to assume leadership positions in the future, and more likely to prioritize family and pursue positions in the traditional nursing field. In total, 425 (84%) respondents stated a Norwegian background. Respondents who stated that both of their parents were born in a country other than Norway made up the 79 (16%) students of immigrant background. Those with immigrant backgrounds were more motivated than other students by income, status and flexible working hours and less likely to pursue a specialization or future employment in the nursing field.